Gastrectomy with or without omentectomy for cT3–4 gastric cancer: a multicentre cohort study. Issue 12 (20th May 2020) - Ri, M.; Nunobe, S.; Honda, M.; Akimoto, E.; Kinoshita, T.; Hori, S.; Aizawa, M.; Yabusaki, H.; Isobe, Y.; Kawakubo, H.; Abe, T.
Abstract : Background: Omentectomy is performed widely for locally advanced gastric cancer to prevent disease recurrence. However, its clinical benefit is unknown. Methods: This retrospective cohort study compared the outcome of gastrectomy with preservation of the omentum (GPO) and gastrectomy with resection of the omentum (GRO) among patients with cT3–T4 gastric cancer who underwent gastrectomy between 2006 and 2012 in one of five participating institutions. A consensus conference identified 28 variables potentially associated with outcome after gastrectomy for the estimation of propensity scores, and propensity score matching (PSM) was undertaken to control for possible confounders. Postoperative surgical outcomes, overall survival and disease recurrence were compared between GPO and GRO. Results: A total of 1758 patients were identified, of whom 526 remained after PSM, 263 in each group. Median follow‐up was 4·9 (i.q.r. 3·1–5·9) years in the GRO group and 5·0 (2·5–6·8) years in the GPO group. The incidence of postoperative complications of Clavien–Dindo grade III or more was significantly higher in the GRO group (17·5 versus 10·3 per cent; P =  0·016). Five‐year overall survival rates were 77·1 per cent in the GRO group and 79·4 per cent in the GPO group ( P =  0·749). There were no significant differences in recurrence rate or pattern of recurrence between the groups. Conclusion: Overall survival and disease recurrence were comparable in patients with cT3–4 gastric cancer who underwent GPO or GRO. Abstract : This study investigated whether omentum‐preserving gastrectomy for locally advanced gastric cancer is non‐inferior to omentum‐sparing gastrectomy, with rigorous adjustment for all known potential confounding factors associated with outcomes. Five‐year overall survival rates were 79·4 and 77·1 per cent respectively. Oncologically, omentum‐preserving and omentum‐resecting gastrectomy yielded similar outcomes. No difference Abstract : Antecedentes: La omentectomía se realiza ampliamente en el cáncer gástrico localmente avanzado para prevenir la recidiva de la enfermedad. Sin embargo, se desconoce su beneficio clínico. Métodos: Este estudio retrospectivo comparó el resultado de la gastrectomía con preservación del omento ( gastrectomy with preservation of the omentum, GPO) con la gastrectomía con resección del omento ( gastrectomy with resection of the omentum, GRO) para el cáncer gástrico con estadio clínico T3/T4. Se incluyeron pacientes sometidos a gastrectomía por cáncer gástrico clínico T3/T4 (2006‐2012) y se recogieron datos relevantes de 5 hospitales participantes. A través de una conferencia de consenso se identificaron 28 variables potencialmente asociadas con el resultado tras la gastrectomía, mediante las cuales se estimaron las puntuaciones de propensión, utilizándose el emparejamiento por puntuación de propensión ( propensity score matching, PSM) para el control de posibles factores de confusión. Los resultados quirúrgicos postoperatorios, la supervivencia global y la recidiva de la enfermedad se compararon entre las gastrectomías con GPO y GRO. Resultados: En total, se identificaron 1.758 pacientes, seleccionándose 526 (263 GRO y 263 GPO) tras el PSM. La mediana (rango intercuartílico) de seguimiento fue de 4, 9 años (3, 1‐5, 9) en el grupo GRO y de 5, 0 años (2, 5‐6, 8) en el grupo GPO. La incidencia de complicaciones postoperatorias de Clavien‐Dindo grado III o más alto fue significativamente más elevada en el grupo GRO que en el grupo GPO (17, 1% versus 9, 1%; P = 0, 010). La supervivencia global a los 5 años fue del 77, 1% para el grupo GRO y del 79, 4% para el grupo GPO ( P = 0, 749). No hubo diferencias estadísticamente significativas en la tasa de recidiva o patrón de recidiva entre ambos grupos. Conclusión: La supervivencia global y la recidiva de la enfermedad son comparables en pacientes con cáncer gástrico estadio clínico T3‐4 sometidos a GPO o GRO.